If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(u + -1) + -1 = -3(-4u + 6) + -1u Reorder the terms: 3(-1 + u) + -1 = -3(-4u + 6) + -1u (-1 * 3 + u * 3) + -1 = -3(-4u + 6) + -1u (-3 + 3u) + -1 = -3(-4u + 6) + -1u Reorder the terms: -3 + -1 + 3u = -3(-4u + 6) + -1u Combine like terms: -3 + -1 = -4 -4 + 3u = -3(-4u + 6) + -1u Reorder the terms: -4 + 3u = -3(6 + -4u) + -1u -4 + 3u = (6 * -3 + -4u * -3) + -1u -4 + 3u = (-18 + 12u) + -1u Combine like terms: 12u + -1u = 11u -4 + 3u = -18 + 11u Solving -4 + 3u = -18 + 11u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-11u' to each side of the equation. -4 + 3u + -11u = -18 + 11u + -11u Combine like terms: 3u + -11u = -8u -4 + -8u = -18 + 11u + -11u Combine like terms: 11u + -11u = 0 -4 + -8u = -18 + 0 -4 + -8u = -18 Add '4' to each side of the equation. -4 + 4 + -8u = -18 + 4 Combine like terms: -4 + 4 = 0 0 + -8u = -18 + 4 -8u = -18 + 4 Combine like terms: -18 + 4 = -14 -8u = -14 Divide each side by '-8'. u = 1.75 Simplifying u = 1.75
| 1/4(3x-1)=2(x-2) | | x/9x=2/3 | | 29/5=k-1/5(-10k-4) | | 4/3x=44 | | 2(x-3)=5(2x+6) | | -6(9x-8)=425 | | (16+a)+11= | | 18+2x=9x+4 | | 2(x+5)=6x+10-4x | | 5(t+3)+9=3t+(-6)+6 | | 3/2(y+2)=g | | 2/3(3x-6)=10 | | 6[3-(4+4x)]=-8+2(1-14x) | | 21x+7=3x+16 | | 4-5x=-26 | | 4/p=16/5 | | 9(m+1)-6m=3m+6 | | 2-5/16 | | 2x8-2+6/3=0 | | 3-4(6+11p)=-7p-58 | | 8x-3y=32 | | 5-8x=19-10x | | -2(8u-9)+6u=5(u+6) | | 4x+14=3x+6 | | -x-9=-6x+36 | | 4(a-2)+4=2a-6 | | 4+1.5x=13 | | 12x^34+3=7 | | -4(-8b+3)=-204 | | z/5+3=7 | | 8-0.25=0.5x+2 | | -3m+w=2m |